2007
DOI: 10.1055/s-2007-966212
|View full text |Cite
|
Sign up to set email alerts
|

Transgastric endoscopic ultrasonography-guided biliary drainage: results of a pilot study

Abstract: EUS-guided hepaticogastrostomy is an efficient technique and could be a future alternative to percutaneous biliary drainage or palliative surgical drainage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
146
0
16

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 227 publications
(165 citation statements)
references
References 12 publications
1
146
0
16
Order By: Relevance
“…A further advantage of a straight stent is the ability to retrieve or exchange the stent over the wire without loss of ductal access. Covered SEMS have been used for transenteric drainage, but may migrate, particularly with shortening [5]. The covering may block drainage of a secondary duct (e.g., cystic duct or intrahepatic branch).…”
Section: Stentsmentioning
confidence: 99%
See 2 more Smart Citations
“…A further advantage of a straight stent is the ability to retrieve or exchange the stent over the wire without loss of ductal access. Covered SEMS have been used for transenteric drainage, but may migrate, particularly with shortening [5]. The covering may block drainage of a secondary duct (e.g., cystic duct or intrahepatic branch).…”
Section: Stentsmentioning
confidence: 99%
“…Both plastic and metal stents have been used for transenteric drainage. Bories et al [5] reported two cases of peritoneal leak caused by shortening of the metal stent after deployment. The available data on EUS-guided choledochoduodenostomy is summarized in Table 5.…”
Section: Available Datamentioning
confidence: 99%
See 1 more Smart Citation
“…However, surgery has been associated with high complication rates and morbidity [2,3] . In recent years various groups have described endoscopic ultrasound guided access of the left system, allowing placement of metal or plastic stents either across the distal stricture or in the stomach (hepatico-gastrostomy), with high technical success guided biliary drainage, various groups mainly from tertiary care academic expert centres have reported similar success rates in small case series [6][7][8] . However, various obstacles still exist to extending the general applicability of this technique outside expert centres.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, plastic stent placement via the puncture site to the target biliary duct is performed in the first session to prevent bile leakage in many reports (2)(3)(4)(5)(6)(7)(8)(9)(10)(11). Only a few case series undergoing ESBD with deployment of a covered self-expandable metal stent (SEMS) in a one-step fashion across the puncture site have been reported because there is a risk of migration of the deployed covered SEMS (5,7,8). Recently, a newly designed fully-covered SEMS with an anti-migration mechanism has become commercially available.…”
Section: Introductionmentioning
confidence: 99%